Are solar tracking technologies feasible for domestic applications in rural tropical Africa? - Kanyarusoke, Kant E.; Gryzagoridis, Jasson; Oliver, Graeme (Journal of Energy in Southern Africa, 2015)
That solar tracking improves energy yields from solar harvest systems is not debatable. Nor is the under powering of tropical Africa amidst plenty of energy resources – including solar. This paper presents a review of recent literature on tracking as applied to domestic solar harnessing devices. The purpose is to find basic requirements in design of a suitable solar tracker for the region’s rural homes. It is concluded that Single axis passive trackers possibly will stand better chances of acceptability in the region.